System-level evaluation of productivity and quality in semiconductor frontend fabrication integrating product and process models - Magnanini, Maria Chiara; Djurdjanovic, Dragan; Pomi, Riccardo; Tolio, Tullio (CIRP journal of manufacturing science and technology, 2025)
In semiconductor manufacturing, photolithography represents the core process of frontend fabrication as the quality outcome in terms of overlay errors depends entirely on it. Hence, particular attention is devoted to the inspection of each wafer layer, having 100 % measurements of markers distributed across a wafer with subsequent long inspection times. At the same time, process control is based on each layer’s overall measurements, discouraging companies from improving productivity by reducing inspection time. As a consequence, in this context, the product, process and system are extremely inter-related. Recent developments in joint product-process modelling show that robust model-based control coupled with optimal down-selection of measurement markers enables improved process control without decreasing the quality. However, when considering the system level effects, new dynamics should be accounted for in order to make decisions about production system configuration and operations. This paper proposes a novel analytical model for the evaluation of quality and productivity performance in manufacturing systems characterized by propagation of quality errors, process adaptation and alternative inspection policies. The proposed model is general, but particularly useful for the semiconductor sector. Application of this method to an industrial-scale semiconductor manufacturing system shows that when product-process-system are considered together, global optimal solutions can be achieved.